Imaginação e desconstrução em K. Stanislávski - Zaltron, Michele Almeida (2011)
This work deals with the importance of deconstruction in Konstantin Stanislávski‟s research, that means, opening space, both in the actor and in the role, in order allow the creative manifestation and the concretion of imagination in the actor‟s body/mind in its most efective way. We initiate our inquiry reflecting on the evolution of K. Stanislávski‟s practical and artistic thought, going through the theatrical context of his time, the main change of perspective that has happened in his research, the elements of his system and their relation with imagination; and the work on the physical actions. We present a study of the image constitution in the actor‟s body/mind and also the imagination in K. Stanislávski‟s actor creative process in different phases of his work. We finish our study by reflecting on the deconstruction/composition of the actor and the character towards deconstructing the unnecessary elements for the creative way and opening possibilities, as well as analyzing the deconstruction of the role to compose the character. We also study the pedagogical theatrical practice of etiud creation and its relation with the active analysis method